The housing price dynamics and macroeconomic factors: Evidence of Taiwan housing market - Hung, Chih-Hsing; Liu, Hui-Chuan; Su, Pei-Jia; Tzang, Shyh-Weir (International Journal of Strategic Property Management, 2025)
The housing price in Taiwan has seen a sharp increase since 2020 after a long period of stability from 2011 to 2019. To provide a more granular analysis on this substantial rise of the housing prices since 2020 in Taiwan, we applied the hedonic pricing model to analyze the completed and presale residential housing across four types of houses: luxury, first-class, second-class and suite. By incorporating relevant macroeconomic variables from 2014 to 2022, we try to capture the demand of homebuyers across the three biggest cities in Taiwan. In the completed housing market, we find that the suite prices in Taipei and Taichung cities are more significantly affected by Taiwan’s continuing economic growth, whereas the suite prices in Kaohsiung city are hindered by its historically stagnant employment market. Notably, suite prices in Kaohsiung display greater sensitivity to construction cost changes and broader economic cycles compared to the suite prices in Taipei and Taichung. These findings highlight the unique dynamics of real estate markets in northern, central, and southern Taiwan, providing valuable insights for housing investors, prospective homebuyers in different regions and policymakers in their decision making.